Spatial heterogeneity and seasonal succession of phytoplankton community in the Cosmonaut Sea, East Antarctica: driving forces and implications - Wu, Guanbei; Li, Dong; Zhao, Jun; Pan, Jianming; Hu, Ji; Yu, Peisong; Sun, Weiping; Zhang, Haifeng; Zhu, Changfeng; Li, Cuiting (Frontiers in Marine Science, 2025)
Understanding the dynamics of the phytoplankton community in the marginal seas of the Southern Ocean is crucial for delineating its role in global carbon cycling. This study investigated spatiotemporal variations in phytoplankton community structure and organic carbon pools in the Cosmonaut Sea, East Antarctica, with an emphasis on spatial heterogeneity and environmental drivers during late austral summer (February). Water samples were collected from 15 stations during the 40th Chinese Antarctic Research Expedition (CHINARE-40, February 2024), and nutrient, pigment, particulate organic carbon (POC), and dissolved organic carbon (DOC) concentrations were quantified. The CHEMTAX analysis revealed that the phytoplankton community was dominated by diatoms (38% ± 16%), dinoflagellates (22% ± 12%), and Prymnesiophyceae Phaeocystis antarctica (12% ± 10%). Diatoms and P. antarctica contributed significantly to POC (r = 0.36, p < 0.01) and DOC (r = 0.69, p < 0.01), respectively. Spatial distribution patterns displayed pronounced heterogeneity; large ice-edge diatoms dominated cold, high-light, and shallow mixed-layer regions, while small pelagic diatoms and dinoflagellates dominated in stratified, nutrient-limited, and low-light environments. Comparative analysis with adjacent Southern Ocean sectors further highlighted how distinct water masses shape niche competition. Furthermore, our results suggest a trend toward phytoplankton miniaturization, with increasing prevalence of dinoflagellates and P. antarctica under projected positive phases of the Southern Annular Mode, potentially diminishing biological carbon pump efficiency and weakening carbon sequestration. Collectively, these findings clarify how the Cosmonaut Sea phytoplankton community responds to environmental variability, providing essential insights into biogeochemical cycling and carbon budget dynamics in the Southern Ocean under climate change.